AmpR is a dual regulator in Stenotrophomonas maltophilia with a positive role in β-lactam resistance and a negative role in virulence, biofilm and DSF production - Alcaraz, Eliana Sabrina (2022)
Stenotrophomonas maltophilia intrinsic resistance to β-lactams is mediated by two chromosomal β-lactamases, L1 and L2, whose induction depends on AmpR. Its quorum sensing (QS) signal, the diffusible signal factor (DSF), has a positive role in biofilm production, virulence and induction of β-lactamases. We hypothesized that AmpR has a role in virulence, biofilm production and QS system. Studies were done on S. maltophilia K279a, K279a ampRFS (ampR deficient mutant) and K279aM11 (constitutively active AmpR mutant). K279a ampRFS showed the highest biofilm biomass, thickness and 3D organization. Conversely, K279aM11 was the least efficient biofilm former strain. qRT-PCR showed that spgM, related to biofilm formation and virulence, was upregulated in K279a ampRFS and downregulated in K279aM11. A constitutively active AmpR led to a reduction of DSF production, while K279a ampRFS was the highest producer. Consequently, qRT-PCR showed that AmpR negatively regulated rpfF expression. K279a ampRFS presented the highest oxidative stress resistance, overexpressed sodA gene and showed the highest virulence in the Galleria mellonella killing assay. This is the first evidence of the function of AmpR as a dual regulator in S. maltophilia with a positive role in β-lactam resistance and a negative role in DSF production, biofilm formation, oxidative stress resistance and virulence.